Long-Term Exogenous Melatonin Treatment Modulates Overall Feed Efficiency and Protects Ovarian Tissue Against Injuries Caused by Ethanol-Induced Oxidative Stress in Adult UChB Rats - Chuffa, Luiz Gustavo A.; Amorim, Joao P. A.; Teixeira, Giovana R. [UNESP]; Mendes, Leonardo O.; Fioruci, Beatriz A.; Pinheiro, Patricia F. F. [UNESP]; Seiva, Fabio R. F. [UNESP]; Novelli, Ethel L. B. [UNESP]; Mello Júnior, Wílson de [UNESP]; Martinez, Marcelo; Almeida-Francia, Camila C. D. [UNESP]; Martinez, Francisco E. [UNESP] (Wiley-Blackwell, 2011)
Background: Chronic ethanol intake leads to reproductive damage including reactive oxygen species formation, which accelerates the oxidative process. Melatonin is known to regulate the reproductive cycle, food/liquid intake, and it may also act as a potent antioxidant indoleamine. The aim of this study was to verify the effects of alcoholism and melatonin treatment on overall feed efficiency and to analyze its protective role against the oxidative stress in the ovarian tissue of UChB rats (submitted to 10% [v/v] voluntary ethanol consumption).Methods: Forty adult female rats (n = 10/group) were finally selected for this study: UChB Co: drinking water only; and UChB EtOH: drinking ethanol at 2 to 6 ml/100 g/d + water, both receiving 0.9% NaCl + 95% ethanol 0.04 ml as vehicle. Concomitantly, UChB Co + M and UChB EtOH + M groups were infused with vehicle + melatonin (100 mu g/100 g body weight/d) intraperitoneally over 60 days. All animals were euthanized by decapitation during the morning estrus (4 AM).Results: Body weight gain was reduced with ethanol plus melatonin after 40 days of treatment. In both melatonin-treated groups, it was observed a reduction in food-derived calories and liquid intake toward the end of treatment. The amount of consumed ethanol dropped during the treatment. Estrous cycle was longer in rats that received both ethanol and melatonin, with prolonged diestrus. Following to oxidative status, lipid hydroperoxide levels were higher in the ovaries of ethanol-preferring rats and decreased after melatonin treatment. Additionally, antioxidant activities of superoxide dismutase, glutathione peroxidase activity, and glutathione reductase activity were increased in melatonin-treated groups.Conclusions: We suggest that melatonin is able to affect feed efficiency and, conversely, it protects the ovaries against the oxidative stress arising from ethanol consumption.
Keywords: Melatonin; Feed Efficiency; Ovary; Ethanol; Lipid Peroxidation